Entrepreneurs’ Innovative Behaviour Response in Rural Tourism Development. A Case Study of Local Service Providers in Dong Van Karst Plateau Geopark, Northern Vietnam - TRUONG, Thi Hang (Journal of Environmental Management and Tourism, 2024)
Tourism industry becomes the spearhead economy in the Vietnamese government's development strategies that compete with regional countries like Thailand, Taiwan, Singapore, Philippines, Malaysia. Especially tourism in rural areas has been focused on and integrated into regional and national development programs in terms of creating a driving force for socio-economic development, high quality, diversified, and branded tourism products. Innovative efforts are necessary to further promote this industry so as to reap the full benefits and potential of this sector. Creativity and innovative approaches are essential for success. The objective of this study is to examine the impact of innovation on the effectiveness of entrepreneurs in the tourism industry and propose that strategic and behavioural innovativeness enhances performance of entrepreneurs. Based on semi-structure interviews with 15 local service providers, the existing business challenges facing the service providers were identified and innovation activities that they adopted in responding to the challenges for the development strategies of rural tourism in Dong Van Karst Plateau Geopark. This research contributes to the understanding of innovative behaviour of participants and also some practical benefits as responses to their business challenges. However, the sample size of the study is quite small, new avenues for further research is highly recommended.